Analisis Teknik Pukulan Drum Set pada Lagu Cold Sweat Karya James Brown - Kundiman, Ryan Sean (Peneliti.net, 2025)
This study aims to analyze the role of rim shoot and ghost notes techniques in shaping dynamic variations in drum set performance in the song